Pengaruh Kemandirian Belajar Dan Perhatian Orang Tua Terhadap Keaktifan Belajar Siswa Pada Mata PelajaranIlmu Pengetahuan Sosial Terpadu Kelas VIII SekolahMenengah Pertama Negeri 1 Jiken Blora Tahun Ajaran 2015/2016 - INDRIASTUTI, IKA FATHUR, Drs. Djumali, M.Pd (2016)
The purpose of this study to determine: 1 ) Effects of independent learning of students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016 , 2 ) the effect of the attention parents to students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016 , and 3 ) the influence of independent learning and attention parents to students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016. This study uses quantitative methods associative. The population in this study were students of VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016 is 230 students. The sampling technique using Simple Random Sampling as many as 139 respondents. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliability testing. Data analysis technique used is multiple linear regression, F test, t-test, R2, and the relative contribution and effective. Results of regression analysis regression equation: Y = 3,751 + 0,531X1 + 0,382X2. The conclusion of this study were: 1) independent learning significantly to students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016. Based on t test obtained t > t table is 6,285 > 1,978 and the significance value < 0.05 is 0.000 , 2) The effect of the attention parents significantly to students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016. Based on t test obtained t > t table is 4.973 > 1.978 and the significance value <0.05 is 0.000. 3)the influence of independent learning and attention parents significantly to students learning activeness in social science subjects VIII class integrated junior high school 1 Jiken Blora the school year 2015/2016. Based on test results obtained F hitung > F table is 150.814> 3.063 at a significance level of 5%. 4) Variable X1 gives the relative contribution of 79,5% and effective contribution of 63.3%, X2 gives the relative contribution of 83,0 % effective contribution of 5.6%. 5) The calculation result R2 obtained 0.689, meaning 68.9 % students learning activiness is influenced by independents learning and attention parents, while the remaining 31.1 % influenced by variables outside the research.